Analisis Hukum Islam terhadap Pembagian Harta sebelum Wafatnya Pewaris: Studi Kasus di Kecamatan Manggala: Analysis of Islamic Law on the Distribution of Assets before the Death of the Heir: A Case Study in Manggala Subdistrict - Nita Zikriani; Abd. Qadir Gassing HT; Abd. Rauf Muhammad Amin (BUSTANUL FUQAHA: Jurnal Bidang Hukum Islam, 2024)
The division of property before the death of the heir in the Manggala sub-district of Makassar city from the perspective of Islamic Law is the subject matter and discussion in this study. Qualitative research is the type of research used in this research with theological-normative syar'i and sociological approaches. And to be able to describe and analyze the problems that occur and produce a conclusion, data collection methods are carried out through observation, interviews and documentation. The results showed that some people in the Manggala sub-district of Makassar city divided their property to the heirs before death, with the assumption that if the property was divided after death it could cause disputes or disputes among the heirs because of unfairness in dividing the inheritance. Although the distribution of property is divided before death, they still term it as inheritance, this is clearly contrary to what is understood in Islamic law, because one of the conditions for inheritance is the death of the heir, while this condition is not fulfilled. The implication of this research is the importance of the community to know the knowledge of inheritance and explain it to the family so as to reduce the impact of disputes in the distribution of inheritance.